IMPACT OF ENDOPHYTIC RALSTONIA SP. FROM ALOE VERA GEL AND ITS ANTIMICROBIAL ACTIVITY - SINHA, ASTHA; PRIYA, RUCHIKA; MADHUMATHY; NIMISHA; W, JABEZ OSBORNE (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective- Isolation of endophytic Ralstonia sp. from Aloe vera gel and its antimicrobial activity. The present study was conducted to determine the significance of endophytic bacteria in Aloe vera gel for the prevention and treatment of various infections caused by bacteria. Methods- The endophytic bacteria from Aloe vera gel were isolated using LB media. The six isolates obtained were found to be gram negative, which was mass multiplied and bacterial secondary metabolites were extracted using various solvents. Antimicrobial activity was detected by agar-well diffusion method and was tested against Pseudomonas aeruginosa, Staphylococcus aureus and E. coli. Bacterial strains were characterized using 16S rRNA technique. Result- Ribosomal database project 10.28 release [RDB] showed that nearest neighbour for VITNARMJ-3 is Ralstonia pickettii, accession no AY741342 [sequence similarity 94.6%]. Cut 0ff <98.7% identical to the nearest neighbour are always members of different species. Conclusion- The bioactive compounds obtained from isolate VITNARMJ3 can be effectively used in food and pharmaceutical industries against various bacterial pathogens. Keywords:Â Endophytes, Aloe vera, Bioactive compounds, Antimicrobial activity, 16S rRNA sequencing